Implementation of Commercial Business License Policy in Downstream Oil and Gas Business Activities in Bitung City - Pontoh, Yumiko Toar; Pangkey, Itje; Mokat, Jetty E. H. (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The purpose of this research is to describe, analyze and describe how the management of the Non-Subsidized Solar Industrial Fuel trading business permit in Bitung City. What are the factors that hinder the processing of Non-Subsidized Fuel Trading Business License for Industrial Solar in Bitung City The research method uses a qualitative approach. Data collection techniques using interviews, documentation studies and observation. The results showed that the commercial business license policy for downstream oil and gas business activities in Bitung City has not been implemented properly because there are business actors who do not take care of the Commercial Business License even though they have been trading in Bitung City and its surroundings. There are obstacles in managing the Commercial Business License in Bitung City, namely the submission of files and management must be done directly to the Ministry of Energy and Mineral Resources because there is no representative authority in Bitung City.